Effects of galvanization on the mechanical properties of high and ultra‐high strength steel tubes. Issue 2 (1st September 2021) - Najafabadi, Esmaeil Pournamazian; Heidarpour, Amin; Raina, Sudhir; Arashpour, Mehrdad; Zhao, Xiao‐Ling
Abstract: A widely used corrosion protection technique for steel structures is hot‐dip galvanizing. This method increases the life of steel structures and reduces maintenance costs. In this technique, steel elements are cleansed through caustic cleaning, rinsing, pickling, and dipping in flux solutions. After cleaning, components are dipped in molten zinc until a protective layer is formed. The galvanizing procedure and its effects on structural mild steel materials have been studied. However, the effects of galvanizing on mechanical properties of high and ultra‐high‐strength steels (HSS and UHSS) have received limited attention. This mechanical investigation is vital since UHSS, and HSS steels are sensitive to heating and cooling cycles, and their mechanical behavior may change when exposed to high‐temperature during hot‐dip galvanizing. To this end, an experimental program was designed and carried out to find out the mechanical behavior of standard coupons taken from UHSS and HSS tubes after galvanizing. HSS and UHSS tubes were cleansed and dipped in a molten zinc bath (460 °C) for 3.0 and 10.0 minutes. For comparison, a mild steel tube with the same dimensions was also galvanized by dipping in zinc for 10.0 minutes. After galvanizing, dog‐bones and short tubes were cut out from the tubes for standard tensile and compressive tests, respectively. The tests revealed that the ultimate tensile strength of HSS and UHSS tubes decreased noticeably while the changes in their yield strengths were not significant. These changes were more significant for longer molten zinc bath dipping times. For HSS and mild steel specimens, the heat exposure had a similar effect as normalizing or annealing done after casting steel. For mild steel, normalizing or annealing increases yield, and ultimate strength and the same thing happened here. It was shown how the observed behaviors and changes were related to the grade of steel materials and their manufacturing process. Finally, optical microscopy was conducted to inspect the micro‐scale properties of the zinc layer. Microscopic results show that under the same zinc dipping time the zinc layer thickness on UHSS and HSS is almost double of that on mild steel which can increase the lifespan of the galvanized parts while decreasing the adhesion of the zinc layer to the steel base.